(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper investigates the effectiveness of educational programs designed to cultivate leadership skills in students. It will explore various program models, including student government, service learning, and leadership development courses. The research will examine how these programs impact students' leadership behaviors, self-efficacy, and critical thinking skills. The paper will discuss the importance of leadership development in education and its potential benefits for future generations.